3D printing of complex shaped alumina parts. Issue 16 (November 2018) - Mamatha, Sirisala; Biswas, Papiya; Ramavath, Pandu; Das, Dibakar; Johnson, Roy
Abstract: Alpha-alumina powder was mixed with methyl cellulose as a binder with concentration as low as 0.25% by weight in an aquoes medium and kneaded in a high shear mixer to obtain a printable paste. The paste was subjected to rheological measurements and exhibited a shear rate exponent of 0.54 signifying the shear thinning behavior. The paste was used for printing parts with various shapes according to CAD model by employing a ram type 3D printer. Printed parts were dried and the green density was determined. Further, the parts were also subjected to X-ray radiography in order to evaluate the possible occurrence of printing defects. The samples were sintered under pressureless condition at 1650 °C in a muffle furnace and Hot Isostsically Pressed (HIP) at 1350 °C and a pressure of 1650 bar using a vacuum encapsulated SS CAN. Hot Isostatic pressing resulted in a higher density of 3.94 g/cc in comparison to 3.88 g/cc obtained under pressureless conditions and also shown superior mechanical properties. HIPing of 3D printed samples not only resulted in possible healing of printing defects as reavealed by X-ray radiography but also enhanced the diffusion at low temperature of 1350 °C leading to finer grain sizes as complemented by the microstructure.